Knowledge, attitude and practice of ethnomedicine in common oral and dental diseases in patients attending IIUM dental polyclinic - Sukmasari, Susi; Kamarudin, Anati Amirah; Ihsan TY, Tengku Nur Fatihah; Ab Halim, Noorhazayti (Elsevier Ltd, 2019)
Information from the user of ethnomedicine is required as the baseline data for further research and to conserve local medicine. To identify the association between knowledge, attitude, and practice (KAP) of ethnomedicine in common oral and dental diseases. A cross-sectional descriptive and analytical study was conducted on patients attending IIUM dental clinic within three months. A total of 87 participants aged 18 and above were conveniently selected to answer quantitative questionnaires. The relationship between knowledge, attitude and practice scores was analysed using Spearman correlation coefficient. The participants were Malay, Chinese, Indian and Others with frequency of 49 (56.3%), 28 (32.2%), 4 (4.6%) and 6 (6.9%), respectively. They were 41.4% male and 58.6% female. 97.7% were educated. The participants were knowledgeable in common oral diseases (96.6%). Knowledge of ethnomedicine was correlated with attitude (rho=0.283, p=0.008) and practice (rho=0.251, p= 0.019), while attitude was correlated with practice (rho=0.436, p=0.000). There was a clear pattern of using ethnomedicine to treat oral and dental diseases with significant correlation between KAP. Therefore, further studies on the efficiency and efficacy of the findings described in this study is highly advisable. Keywords: Knowledge; Attitude; Practice; Ethnomedicine; Common Oral and Dental Diseases